Cosmological accents in Paul’s Epistle to the Romans in the light of ecological concerns : antecedents and later developments - Adebayo, Oluwarotimi Paul (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.